UPAYA HUKUM BANDING DALAM PERKARA PERCERAIAN MENURUT HUKUM ACARA PERDATA - Lubis, Fauziah; Safwah, Raiva; Munthe, M.Ridho Pratama; Harahap, Hafni Meylani; Rozi, Fahrur; Rahmi Siregar, Dina Aulia (Gapenas Publisher, 2025)
This study aims to assess the effectiveness of appellate remedies in divorce cases as a legal mechanism that protects individuals who disagree with or are dissatisfied by decisions made by the court of first instance. Within the framework of Indonesia’s civil procedural law, appeals function as a corrective measure to address potential judicial errors in the application of law or the evaluation of facts. The research focuses on the normative legal basis of the appellate process as regulated in the Herziene Indonesisch Reglement (HIR), Rechtsreglement voor de Buitengewesten (RBg), Law Number 48 of 2009 on Judicial Power, and the amended Law Number 7 of 1989 concerning Religious Courts. Additionally, the study examines the implementation of Supreme Court Regulation (PERMA) Number 1 of 2019, which introduces the use of electronic systems for filing appeals. Appeals in divorce cases are commonly initiated due to disputes over divorce rulings, child custody, division of marital property, or alimony determinations considered disproportionate. This research employs a normative juridical approach with qualitative analysis, relying on secondary data sources including primary legal materials such as statutes and court decisions, as well as secondary sources like legal literature and academic journals. The findings indicate that the appellate mechanism plays a vital role in ensuring tiered justice and provides an important avenue for parties who feel aggrieved to seek a review of decisions perceived as legally or substantively flawed.